Combined radiological and surgical management of spinal dural fistulas. (4th July 2015) - Sri, Denosshan; Higgins, Nick; Laing, Rodney
Abstract: Introduction. Spinal Dural Fistulas (SDAVF) are the most common Spinal Vascular Malformation. The management of SDAVFs involves diagnosis and localisation with MRI and spinal angiography and subsequent embolisation or surgical interruption. We report our experience in treating these fistulas in which we undertake endovascular treatment, if technically feasible, with recourse to surgery only if occlusion is not possible. Method. This retrospective study reviews the management of 38 patients treated for SDAVFs over a 13-year period (1997–2010). Patient demographics, procedure and follow-up over a 6–12-month period (mean of approximately 10 months) were analysed and a qualitative assessment of patient outcome was made. Results. Patient ages ranged from 20 to 86 (mean 63.5), with 27 male and 11 female patients. A total of 28 patients managed with a combination of embolisation and surgery report either with improved symptoms or a return to normal. The presence of bladder and bowel symptoms indicated more severe disability and their presence at presentation was associated with lack of improvement following treatment. Conclusions. We report a treatment strategy for SDAVF involving primary endovascular intervention and reserving surgery for those patients in whom endovascular treatment is not possible.